Effect of the Implementation of a Surgical Care Bundle in the Incidence of Surgical Site Infection in Spine Surgery: A Quasi-Experimental Study. Issue 8 (30th August 2021) - Vicente-Sánchez, Gema; Alonso-García, Marcos; Hijas-Gómez, Ana Isabel; González-Díaz, Rafael; Martinez-Martín, Javier; Fahandezh-Saddi, Homid; Durán-Poveda, Manuel; Gil-de-Miguel, Angel; Rodríguez-Caravaca, Gil
Abstract : Quasi-experimental study evaluating the effect of a Clinical Safety and Quality Improvement Plan on the incidence of surgical site infection (SSI) in spinal fusion surgery. There was a decrease in the SSI incidence, and improvements in antibiotic prophylaxis adequacy and preoperative care after the introduction of the care bundle. Abstract : Study Design: Quasi-experimental intervention study. Objective: To assess the effect of a clinical safety and quality improvement plan for patients undergoing spinal fusion surgery on the incidence of surgical site infection (SSI). Summary of Background Data: In recent years, infection surveillance and control programs based on care bundles have been included in surgical protocols. These have proven to be essential tools for the prevention and control of SSI, providing indicators for improvement and allowing the characterization of related risk factors. Methods: A quasi-experimental study was carried out with analysis before and after the introduction of a preventive care bundle (clinical safety and quality improvement plan). Patients who underwent spinal fusion surgery were included. The incidence of SSI up to 90 days after surgery (maximum incubation period) was assessed. The effect of the intervention was evaluated with the adjusted odds ratio (oR) using a logistic regression model. Results: A total of 1554 patients were included, 690 in the period 2007 to 2011 (before) and 864 during 2012 to 2018 (after). SSI incidence decreased from 4.2% to 1.9% after the plan (OR: 0.43; 95% confidence interval: 0.23–0.80; P   =  0.006). There was also an improvement in the adequacy of antibiotic prophylaxis, preoperative preparation, and hair removal procedure after the introduction of the care bundle. Conclusion: After implementation of the care bundle, the incidence of SSI in spine fusion surgery decreased significantly. Multivariate analysis showed that the care bundle was an independent protective factor. The implementation of these measures should be reinforced on the routine medical practice to reduce the SSI incidence. Level of Evidence: 3